Addition of Dehacide 267 As an Anti-Fungal Smart Material on the Body Coating of the MV3 Garuda Limousine - Wibowo, Muhammad Naufal Rizky; Kurniadi, Tedi; Wiratama, Minandre; Hardian, Arie (MUNISI: Military Mathematics and Natural Sciences, 2025)
Military vehicles, such as the MV3 Garuda Limousine, operate in harsh environments that often lead to fungal growth, degrading the protective body coating. This study addressed the issue by integrating Dehacide 267, a non-oxidizing biocide composed of a synergistic combination of isothiazolines and bronopol, into an acrylic-based coating. The coating, prepared with a 2% (w/w) biocide concentration, was tested for antifungal efficacy against Aspergillus niger and Penicillium chrysogenum. The results confirmed that the addition of Dehacide 267 significantly inhibited fungal growth. The biocide achieved up to 95% inhibition after four weeks, demonstrating high effectiveness in preventing fungal colonization. The proposed mechanism of action involves damaging the fungal cell membrane, which is consistent with the biocide’s properties. Furthermore, testing showed that the biocide-enhanced coatings exhibited superior resistance to UV rays and rain, indicating improved structural durability. This research establishes Dehacide 267 as an effective antifungal smart material for specialized vehicle coatings.